2004
DOI: 10.1017/s0950268803001626
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Streptococcus pneumoniae isolates from Argentinian children: serotypes, families of pneumococcal surface protein A (PspA) and genetic diversity

Abstract: PspA is an antigenically variable virulence factor of Streptococcus pneumoniae that inhibits complement deposition and is a potential candidate for human vaccines. Of 64 published strains 96% are in PspA families 1 and 2; optimal protection is family-specific. Effective development of a PspA-containing vaccine requires more information about the PspA family of strains in parts of the world where the vaccine is most needed. In these studies we observed that of 149 isolates (of 19 capsular types) from Argentina,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 29 publications
3
27
0
2
Order By: Relevance
“…We were able to demonstrate differences in the amounts of PspA-specific antibody that bound to different isolates. These results provide additional support for the hypothesis that the ideal PspA-based subunit vaccine should contain at least one member of each of the major PspA families in order to ensure the elicitation of protective immunity against 90% or more of pneumococci (30,39,40,48).…”
Section: Discussionmentioning
confidence: 52%
“…We were able to demonstrate differences in the amounts of PspA-specific antibody that bound to different isolates. These results provide additional support for the hypothesis that the ideal PspA-based subunit vaccine should contain at least one member of each of the major PspA families in order to ensure the elicitation of protective immunity against 90% or more of pneumococci (30,39,40,48).…”
Section: Discussionmentioning
confidence: 52%
“…S3). Because PspA family 2 (clades 3 through 5) and family 1 (clades 1 and 2) constitute 94 to 99% of clinical isolates of pneumococci (14,(44)(45)(46)(47)(48)(49), we also challenged mice with the strain 3JYP3670, which expresses PspA belonging to clade 4 of family 2 (10). Unlike mice inoculated with cCHPBoHc/A, PspA alone, or PBS only, mice nasally immunized with cCHP-PspA were protected from lethal challenge with 3JYP3670 (PspA of clade 4) (10), as was the case with Xen10 expressing PspA of clades 1 and 2 (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This region, also referred to as the B window or clade-defining region (CDR), was the basis for the classification of PspA into six clades, which were grouped into three families (10). Surveillance studies show that PspA from families 1 and 2 are present in 94 to 99% of the isolates in different countries in the Americas (1,2,17,25), with prevalence rates of about 50% each (10,19,25). Previous studies have shown that the level of cross-reactivity among different PspA fragments roughly follows the degree of similarity among the amino acid sequences within the CDR, with a tendency for a higher degree of cross-reactivity among PspA fragments within the same family, rather than between families (16).…”
mentioning
confidence: 99%